AFM Analysis Enables Differentiation between Apoptosis, Necroptosis, and Ferroptosis in Murine Cancer Cells - Van der Meeren, Louis (iScience, 2020)
Regulated cell death (RCD) has a fundamental role in development, pathology, and tissue homeostasis. In order to understand the RCD mechanisms, it is essential to follow these processes in real time. Here, atomic force microscopy (AFM) is applied to morphologically and mechanically characterize four RCD modalities (intrinsic and extrinsic apoptosis, necroptosis, and ferroptosis) in murine tumor cell lines. The nano-topographical analysis revealed a distinct surface morphology in case of necroptosis, ∼ 200 nm membrane disruptions are observed. Using mechanical measurements, it is possible to detect the early onset of RCD. Combined elasticity and microrheology analysis allowed for a clear distinction between apoptotic and regulated necrotic cell death. Finally, immunofluorescence analysis of the cytoskeleton structure during the RCD processes confirm the measured mechanical changes. The results of this study not only demonstrate the possibility of early real-time cell death detection but also reveal important differences in the cytoskeletal dynamics between multiple RCD modalities.